2023
DOI: 10.3389/fneur.2022.1076993
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for neuropathic pain: A meta-analysis of randomized control trials

Abstract: BackgroundNeuropathic pain (NP) is expected to increase due to the high risk of global population aging. Acupuncture has a definite clinical effect on NP. Therefore, a systematic review and meta-analysis were conducted to evaluate the effect on pain intensity and safety of acupuncture in patients with NP.MethodsAn encompassing search of specific authoritative databases in English, from their inception to 2022, was performed. The databases were as follows: Scopus, Ovid EMBASE, Ovid Cochrane Database of Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Moderate level evidence suggests favorable utilization of acupuncture as an optional treatment for PDN. [117][118][119][120] Numerous prospective clinical studies and RCTs suggest a positive effect with relatively low adverse event rates. 119,[121][122][123][124][125] A singleblinded, placebo-controlled RCT compared acupuncture to sham acupuncture demonstrated low-moderate treatment effect without appreciable side effects, meanwhile another RCT found that pain was improved at week 12 of follow-up but efficacy waned by week 18 when acupuncture was compared to standard of care.…”
Section: Section 4 Alternative Approachesmentioning
confidence: 99%
“…Moderate level evidence suggests favorable utilization of acupuncture as an optional treatment for PDN. [117][118][119][120] Numerous prospective clinical studies and RCTs suggest a positive effect with relatively low adverse event rates. 119,[121][122][123][124][125] A singleblinded, placebo-controlled RCT compared acupuncture to sham acupuncture demonstrated low-moderate treatment effect without appreciable side effects, meanwhile another RCT found that pain was improved at week 12 of follow-up but efficacy waned by week 18 when acupuncture was compared to standard of care.…”
Section: Section 4 Alternative Approachesmentioning
confidence: 99%
“…Research, including a meta-analysis, has shown that acupuncture, along with massage, provides superior outcomes compared to traction therapy and traditional Chinese medicine in the context of lumbar disk herniation treatment ( Mo et al, 2019 ). Feng et al (2023) reported that acupuncture was more effective in reducing pain intensity compared to sham interventions or no treatment, and adverse events related to acupuncture were mild and reversible. Furthermore, clinical evidence suggests that acupuncture delivers better short-term relief of leg pain in patients suffering from chronic discogenic sciatica than sham acupuncture ( Huang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%